Implementasi Manajemen Risiko di Masa Pandemi COVID-19 - Yuliana Yuli; Defrizal Defrizal; Hasbullah Hasbullah (Jurnal Manajemen dan Bisnis (JMB), 2022)
The purpose of this research, is to see the implementation of risk management carried out by MSMEs in the Pagi Market and Sentral Market in North Lampung Regency during the COVID-19 pandemic that emerged since March 2020. This research explain how MSME owners identify risks, conduct risk analysis and evaluate risks, and also see how MSME owners as well as treat these risks during the COVID-19 pandemic. This research is a case study on 10 MSMEs located in the Pagi Market and Sentral Market in North Lampung Regency. Data obtained through interview and checklist methods, then data will be analyzed using ISO 31000:2018 risk management process guidelines (identifying risks, analyzing and evaluating risks, and as well as treating risks that arise).By obtaining the result of the analysis and research conducted, the results obtained are: 1) Almost of the respondents do not or have not identify risk. 2) The results of the analysis risk and evaluation carried out show that almost all of the identified risks are in the green zone (low risk). For MSMEs that are included in the red zone, it is MSMEs engaged in the retail business and culinary business 3) Many respondents choose to maintain risk.